Sistema de procesamientos administrativos y operativos de la unidad de docencia, investigación y vinculación de cacao de la ESPAM MFL - Delgado Carranza, Johanna Elizabeth (2012)
This research is meant to be a support tool for the development of administrative and operational activities of the Teaching Unit, Research and Linking Cocoa (TURLC), the group in a simple, orderly, sequential and standardized operations therein play. The diagnosis was made of the current situation regarding administrative and operational forms, the same ones that were based on the application of data collection as it was recorded on an observation, the interviews Director of Planning, Production Manager, Director of Career and unit coordinator, likewise the survey of students in second through tenth semester of Agricultural Race, in order to identify the problem, as a result of the applied tools identified the lack of a System and Administrative Procedures contribute to operational efficiency efforts. Bearing this in mind we have designed a Manual of Administrative and Operational Procedures that groups the main activities and tasks within and outside the unit also includes specific organizational structure that allows it to better communication, routine functions and processes administrative and operating in a logical and sequential becoming a management tool, to provide the proper use of natural, human, financial and material efficiency to help meet the goal of the unit is to recognize and ensure academic autonomy of self-management and economic and administrative.